Research on power correction control methods for diesel locomotives operating at high altitudes - ZHAO Gang (机车电传动)
This paper introduced in detail the theoretical basis, control effects, and limitations associated with existing power correction control methods for plateau diesel locomotives in different application scenarios, and proposed an adaptive power control strategy, considering the power correction requirements of diesel locomotives operating at high altitudes as the design input. Through a thorough examination of operating characteristics of diesels and complex operating conditions at high altitudes, an algorithmic model was established to capture the relationships between diesel power outputs and parameters such as altitude, ambient temperatures, supercharger exhaust temperatures, and supercharger speeds. Subsequently, a full-scenario adaptive diesel power correction control algorithm was designed, taking into account the fluctuating features in post-intercooling temperature differences between the leading and other locomotives while operating under coupled conditions in tunnels. Furthermore, the validity of the proposed algorithm was verified through field experiments, where the power outputs of the diesels were maximized while ensuring their operational reliability.